Application of neural networks to prediction of company future development - Dvořáková, L.; Vochozka, M. (Математичне моделювання в економіці, 2015)
Application of neural networks to prediction of company future development is much more conceivable now than before. Exploitation of data is one of the most important parts of possible prediction of company development. There are a lot of possibilities how to apply such data and what particular neural network to chose. Development of neural networks dates from 1943 when Perceptron was described and a lot of neural networks have been developed since then. New hybrid neural networks, which are often more accurate than only single-layer and multi-layer networks are being developed even now. The way how they can learn and assess data is substantial for their application in economy.